2020
DOI: 10.3390/molecules25030561
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Spectroscopic Markers of DNA Damage

Abstract: Every cell in a living organism is constantly exposed to physical and chemical factors which damage the molecular structure of proteins, lipids, and nucleic acids. Cellular DNA lesions are the most dangerous because the genetic information, critical for the identity and function of each eukaryotic cell, is stored in the DNA. In this review, we describe spectroscopic markers of DNA damage, which can be detected by infrared, Raman, surface-enhanced Raman, and tip-enhanced Raman spectroscopies, using data acquire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…A similar observation has been described for pulmonary hypertension rat model [51]. Sofińska et al reported that increasing intensity of phosphate vibration indicates DNA fragmentation [52]. High kidney DNA fragmentation has .…”
Section: Discussionsupporting
confidence: 73%
“…A similar observation has been described for pulmonary hypertension rat model [51]. Sofińska et al reported that increasing intensity of phosphate vibration indicates DNA fragmentation [52]. High kidney DNA fragmentation has .…”
Section: Discussionsupporting
confidence: 73%
“…Further, UV light also has an antimicrobial effect on the RNA of viruses, including coronaviruses ( 5 ), which further increases our need to understand the chemical basis for the biological effects of UV light. DNA damage, such as deamination, oxidative damage, strand breaks, and dimer formation, can hinder normal functioning of a cell, prevent DNA replication, and cause cell death ( 6 ). UV-induced DNA damage results mainly in damage to pyrimidine bases, thus inducing the formation of cyclobutane pyrimidine dimers (CPDs), pyrimidine(6-4)pyrimidone photoproducts, and Dewar isomers ( 7 ).…”
mentioning
confidence: 99%
“…Multimodal imaging could be used to monitor oxidative stress, a common consequence of exposure to some toxicants, including nanoparticles, in cells and organoid models through DNA damage and changes in lipid peroxidation. 38 For this, Raman can monitor DNA conformational changes following several bands between 600 and 1700 cm –1 , 39 while MSI can monitor lipid peroxidation by identifying lipid species and their degree of saturation. 40 Therefore, cell response can be characterized in situ as a living system (with VSI) and as a frozen metabolic state (with MSI).…”
Section: Multimodal Imaging and Its Transition To The Clinicmentioning
confidence: 99%